PENGARUH REKRUTMEN, PELATIHAN DAN PENGALAMAN KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN DI PT. MARKETAMA INDAH - Suryono Efendi; Ogy Winenriandhika (GoAcademica Research dan Publishing, 2021)
The purpose of this study is to see whether recruitment, training, work experience affects job satisfaction and its impact on employee performance. The approach used in this research is descriptive analysis and data processing using Structural Equation Modeling (SEM) Techniques. The sample of this study was 115 employees. The results show that recruitment, training, and work experience have a significant effect on employee performance through job satisfaction. Job satisfaction has a full mediating effect (full mediation) between training and employee performance. This company can increase the variables that need to be used in the future.